Artificial Intelligence dalam E-Konseling: Analisis Peran, Dampak, dan Tantangan Etika melalui Systematic Literature Review - Zona Dwi Septianti (PT. PENERBIT TIGA MUTIARA, 2026)
The advancement of digital technology has accelerated the adoption of Artificial Intelligence (AI) in e-counseling services to enhance the accessibility and efficiency of psychological support. While offering numerous benefits, the use of AI also presents challenges related to the quality of therapeutic relationships, privacy, data security, and ethical considerations. This study aims to analyze the role of AI, its impacts, and the ethical challenges emerging in e-counseling services through a Systematic Literature Review (SLR) approach. Data were collected from Google Scholar, GARUDA, ScienceDirect, SAGE Journals, and Crossref, covering publications from 2018 to 2026. The review of 13 selected articles revealed that AI serves as a supportive tool through chatbots, data analytics, preliminary assessments, and automated response systems that help expand access to counseling services and improve service responsiveness. The implementation of AI contributes positively by increasing efficiency and accessibility; however, it remains limited in understanding emotions, demonstrating empathy, and comprehending clients’ psychological contexts. The findings also indicate that privacy, data security, algorithmic transparency, and accountability constitute the primary ethical challenges that require careful attention. This study concludes that AI is more appropriately positioned as a complement to counselors rather than a substitute for human counselors. The novelty of this study lies in its integrated analysis of the roles, impacts, and ethical challenges of AI within a single framework, thereby providing a more comprehensive understanding of the development of e-counseling based on collaborative interaction between technology and professional counselors.